PERANCANGAN KERANGKA PENGUKURAN KINERJA BALANCED SCORECARD DENGAN METODE QUALITY FUNCTION DEPLOYMENT PADA PT. MML - Rudy Vernando Silalahi; Helena Juliana Kristina; Shelvia Shelvia (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2018)
PT. MML as electronic retail company was founded in 2010. This company doesn’t have performance measurement that can cover the whole company performance that is needed. Moreover, the system of performance measurement is partial. The outcome of measurement is only evaluated by related manager and it doesn’t involve other department manager thus improvement that is conducted, doesn’t notice the other impact that is given to another department performance. On that word, designing Balanced Scorecard performance measurement framework with Quality Function Deployment method is required to framework of performance measurement as integrated strategic measurement tool for all departments. In designing that framework needs some data such as interview data, and questionnaire data which is intended to Top Manager for determining performance measures, customer and staff for determining performance driver by using type of sampling is simple random sampling. Besides, matrix of House of Quality roles to decide performance measure with its performance driver, while matrix of QFD II roles to design strategic map and diagram of cause-effect relationship. Based on simulation the result of performance measurement for financial perspective is 3.1 (quite good), customer perspective is 3.51 (good), internal business process perspective is 4.27 (very good), learning and growth perspective is 4.33 (very good). Keyword : Kerangka pengukuran kinerja, Balanced Scorecard, Quality Function Deployment